Sex offender registration and notification act with adolescents adjudicated for illegal sexual behavior: a therapeutic jurisprudence perspective - Alexander, Apryl; Falligant, John Michael; Marchi, Cory; Floding, Erica; Jennings, Marissa (Frontiers in Psychiatry, 2023)
Adolescents adjudicated for illegal sexual behavior (AISB) are subjected to the same Sex Offender Registration and Notification Act (SORNA) policies as adults with sexual offense histories despite current research documenting their relatively low likelihood of recidivism. Therapeutic jurisprudence is a framework which suggests the law should value psychological well-being and strive to avoid imposing anti-therapeutic consequences. The purpose of this article is to analyze the use of SORNA policies with AISB from a therapeutic jurisprudence perspective. Given the current literature documenting the collateral consequences of SORNA on AISB and their families and the lack of efficacy in reducing recidivism, we argue SORNA should not be applied to children and adolescents. We conclude with a discussion of future directions for the juvenile justice system and public policy reform.